Efficacy of Intravenous Tranexamic Acid in Reducing Perioperative Blood Loss and Blood Product Transfusion Requirements in Patients Undergoing Multilevel Thoracic and Lumbar Spinal Surgeries: A Retrospective Study - Todeschini, Alexandre B.; Uribe, Alberto A.; Echeverria-Villalobos, Marco; Fiorda-Diaz, Juan; Abdel-Rasoul, Mahmoud; McGahan, Benjamin G.; Grossbach, Andrew J.; Viljoen, Stephanus; Bergese, Sergio D. (Frontiers in Pharmacology, 2020)
Introduction: Acute perioperative blood loss is a common and potentially major complication of multilevel spinal surgery, usually worsened by the number of levels fused and of osteotomies performed. Pharmacological approaches to blood conservation during spinal surgery include the use of intravenous tranexamic acid (TXA), an anti-fibrinolytic that has been widely used to reduce blood loss in cardiac and orthopedic surgery. The primary objective of this study was to assess the efficacy and safety of intraoperative TXA in reducing estimated blood loss (EBL) and red blood cell (RBC) transfusion requirements in patients undergoing multilevel spinal fusion. Material and Methods: This a single-center, retrospective study of subjects who underwent multilevel (≥ 7) spinal fusion surgery who received (TXA group) or did not receive (control group) IV TXA at The Ohio State University Wexner Medical Center between January 1st, 2016 and November 30th, 2018. Patient demographics, EBL, TXA doses, blood product requirements and postoperative complications were recorded. Results: A total of 76 adult subjects were included, of whom 34 received TXA during surgery (TXA group). The mean fusion length was 12 levels. The mean total loading, maintenance surgery and total dose of IV TXA were 1.5 mg, 2.1 milligram per kilo (mg/kg) per hour and 33.8 mg/kg, respectively. The mean EBL in the control was higher than the TXA group, 3,594.1 (2,689.7, 4,298.5) ml vs. 2,184.2 (1,290.2, 3,078.3) ml. Among all subjects, the mean number of intraoperative RBC and FFP units transfused was significantly higher in the control than in the TXA group. The total mean number of RBC and platelet units given to subjects in the control group was 8.1 (6.6, 9.7) and 7.7 (6.1, 9.4) compared with 5.1 (3.4, 6.8) and 4.6 (2.8, 6.4), respectively. Consequently, there was no statistical difference in postoperative blood product transfusion rates between both groups. There were no significant differences in postoperative incidences of complications within a 30-day period between both groups (Table 4). Conclusions: Our results suggested that the prophylactic use of TXA could reduce intraoperative EBL and RBC unit transfusion requirements in patients undergoing multilevel spinal fusion procedures ≥7 levels.